2010
DOI: 10.1074/jbc.m110.159103
|View full text |Cite
|
Sign up to set email alerts
|

Cell Membrane-bound Kaposi's Sarcoma-associated Herpesvirus-encoded Glycoprotein B Promotes Virus Latency by Regulating Expression of Cellular Egr-1

Abstract: One of the important questions in the field of virus research is about the balance between latent and lytic cycles of replication. Kaposi's sarcoma-associated herpesvirus (KSHV) remains predominantly in a latent state, with only 1-3% of cells supporting a lytic replication at any time. KSHV glycoprotein B (gB) is expressed not only on the virus envelope but also on the surfaces of the few cells supporting lytic replication. Using co-culture experiments, we determined that expression of KSHV gB on as few as 1-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 71 publications
3
49
0
Order By: Relevance
“…However, enhanced cellular Egr-1 and viral RTA expression during early stages of primary infection (Fig. 3) is not sufficient to trigger a lytic infection [6]. These results suggest the following: (i) the role of Egr-1.RTA signaling in initiating a lytic cycle of infection during the course of initial infection of cells is limited; and (ii) there is a missing element in the Egr-1.RTA driven cellular events critical for inducing a productive replication.…”
Section: Discussionmentioning
confidence: 97%
“…However, enhanced cellular Egr-1 and viral RTA expression during early stages of primary infection (Fig. 3) is not sufficient to trigger a lytic infection [6]. These results suggest the following: (i) the role of Egr-1.RTA signaling in initiating a lytic cycle of infection during the course of initial infection of cells is limited; and (ii) there is a missing element in the Egr-1.RTA driven cellular events critical for inducing a productive replication.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the shear rate of the shear product DRz dissociation process is relatively small [45, 46]. The RNA of the DNA-RNA hybrid molecules can be degraded by the RNA enzyme H. Hence, the DNA enzyme can not only directly kill the target RNA such as Rz, but also cause the hydrolysis of the RNA enzyme H to target RNAs, such as ASODN [47, 48]. …”
Section: Discussionmentioning
confidence: 99%
“…Envelope glycoprotein gB interacts with a variety of cell surface molecules including heparan sulfate and integrins to facilitate virus binding and entry [9, 17]. There is growing evidence that demonstrates significant roles of gB interactions to modulate a variety of cell signaling pathways to induce a cellular state that is receptive for virus replication [13, 14, 23, 37]. In a recent study, we demonstrated cell membrane-associated gB to promote adhesion over migration of infected cells via RGD motif [13].…”
Section: Discussionmentioning
confidence: 99%